Sensitive protein detection using an optical fibre long period grating sensor anchored with silica core gold shell nanoparticles - Marques, Leonel M.; Hernandez, Francisco U.; Korposh, Sergiy; Clark, Matt; Morgan, Stephen P.; James, Stephen W.; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2014)
An optical fibre long period grating (LPG), modified with a coating of silica gold (SiO2:Au) core/shell nanoparticles (NPs) deposited using the layer-by-layer (LbL) method, was employed for the development of a bio-sensor. The SiO2:Au NPs were electrostatically assembled onto the LPG with the aid of a poly(hydrochloride ammonium) (PAH) polycation layer. The LPG sensor operates at the phase matching turning point to provide the highest sensitivity. The SiO2:Au NPs were modified with biotin, which was used as a ligand for streptavidin (SV) detection. The sensing mechanism is based on the measurement of the refractive index change induced by the binding of the SV to the biotin. The lowest detected concentration of SV was 19 nM using an LPG modified with a 3 layer (PAH/SiO2:Au) thin film.
Copyright ©2014 Society of Photo-Optical Instrumentation Engineers. This paper was published in the Proceedings of SPIE and is made available with permission of SPIE. One print or electronic copy may be made for personal use only. Systematic electronic or print reproduction and distribution, duplication of any material in this paper for a fee or for commercial purposes, or modification of the content of the paper are prohibited.
Keywords: Long period grating; Bio-sensor; Antigen-antibody; Silica-gold core/shell nanoparticles; Layer-by-layer